Study on Optimization of Pump Shaft Transmission System of Plastic Centrifugal Pump - Lili Zhang; Lingfeng Tang; Qingzhao Wen; Wenbin Luo (Journal of Engineering)
At present, the design of the pump shaft transmission system mostly refers to the design method of the metal pump transmission system. The dynamic and static characteristics of the plastic centrifugal pump are not related to the structural parameters of the pump shaft. Aiming at the influence of the structural parameters of the pump shaft transmission system on the dynamic and static performance of the plastic centrifugal pump, the three-dimensional model of the impeller and volute chamber was drawn by Creo5.0. The CFD calculation of the load of the plastic centrifugal pump was carried out. The flow field of the plastic centrifugal pump under ideal working conditions was simulated by ANSYS FLUENT. Combined with the application principle of singular function in mechanics, the mathematical model of a deflection of the pump shaft transmission system was constructed. Considering the minimum deflection and the maximum critical speed of the first order as the objective function, an optimization model of the structural parameters of the pump transmission system was established. The NSGA-II multiobjective optimization method was used to solve the optimal structural parameters of the optimization model, and the optimization design of the pump shaft span, cantilever, front, and rear bearing clearance was completed. The optimal span cantilever ratio of the rotor model of the single span cantilever structure was 1:0.75. Compared with the traditional design model, the optimized pump shaft deflection is reduced by 52.35%, and the first-order critical speed is increased by 42.77%. Simultaneously, using polynomial fitting as a mathematical tool, the experimental data were analyzed, and the mathematical expression of the rotation speed deflection relationship of the pump shaft at the first critical rotation speed and the corresponding function curve was obtained.